ОСОБИСТИЙ НЕМАЙНОВИЙ ІНТЕРЕС ЯК ФОРМА ДОЗВІЛЬНОЇ ПОВЕДІНКИ У ЦИВІЛЬНОМУ ПРАВІ - Stephanchuk, R.O. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2007)
The concept, legal natures, role and value of personal non-property interest as a form of permissive behavior in the civil law are revealed in article. A special attention is given to definition of permissive behavior forms, and, to interrelation between the personal non-property interest and the subjective personal non-property right. The analysis of world and domestic experience in legitimation of «personal non-property interest protected by the law» is made and the author’s opinion about the system of legal sanctions in the sphere of satisfaction of personal non-property requirements is offered.